Synergistic flame retardant with core-shell structure as well as preparation and application of synergistic flame retardant
Ammonium polyphosphate and titanium dioxide are prepared into composite flame retardant fillers through in-situ polymerization, and coated with organic polymers to form a core-shell structure, solving the problems of low flame retardant efficiency and environmental friendliness of traditional flame retardant, and realizing the in-depth and comprehensive flame retardant in-depth flame retardant Efficient application in molded silicone rubber.
Patent Information
- Application Number
- CN202411394608.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2024-12-31
AI Technical Summary
Traditional flame retardants have problems with low flame retardant efficiency, harmful to the environment and restricted application in addition molded silicone rubber, and the prior art has failed to effectively solve these problems.
In-situ polymerization method is used to prepare ammonium polyphosphate and titanium dioxide into composite flame retardant fillers, and coat them with organic polymers to form a core-shell structure. Titanium dioxide serves as a catalyst to promote decomposition and photocatalytic reactions, avoid platinum catalyst poisoning, and improve flame retardant efficiency.
The flame retardant is achieved with a small amount of added, high flame retardant performance and environmentally friendly flame retardant, ensuring stable application and efficient combustion performance in addition molded silicone rubber.
Smart Images

Figure BDA0005073408570000131
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of flame retardant preparation and application, and specifically relates to a synergistic flame retardant with a core-shell structure and a preparation method and application thereof. Background Art
[0002] With the development of science and technology and people's increasing attention to safety, flame retardancy has become one of the important performance requirements of many materials. However, traditional flame retardants have some limitations. For example, conventional inorganic flame retardants such as aluminum hydroxide and magnesium hydroxide not only have a great impact on material properties due to the large amount of addition, but also have the problem of low flame retardant efficiency. Organic flame retardants such as halogen-containing flame retardants will release toxic gases when burned, which is not only harmful to human health, but also has adverse effects on the environment. Ammonium polyphosphate has the characteristics of high flame retardant efficiency, good thermal stability and low toxicity due to its decomposition absorption of heat, isolation of oxygen and inhibition of free radical reactions. It has a wide range of applications in the field of flame retardants, but it contains a large amount of P and N elements. When used in addition silicone rubber, it will cause the platinum catalyst to fail due to poisoning.
[0003] Chinese patent document CN 105037804 A provides a method for preparing a core-shell synergistic silicon-magnesium composite flame retardant, which is used for EVA plastics. The flame retardant filling amount of the EVA plastics that meet the flame retardancy UL94-V0 level must reach 50wt%.
[0004] Chinese patent document CN 106120431 A provides a flame retardant and smoke suppression plant fiber paper-based material and a preparation method thereof, wherein the ammonium polyphosphate-diatomaceous earth / nano titanium dioxide composite flame retardant prepared by in-situ polymerization can give full play to the synergistic flame retardant effect between ammonium polyphosphate and silicon and titanium elements, and has a good flame retardant effect. However, the exposed P and N substances are not coated, which limits its application in addition silicone rubber.
[0005] Chinese patent document CN 114773681 A uses melamine urea-formaldehyde resin as the shell material to perform in-situ polymerization to microencapsulate the modified cyclotriphosphazene flame retardant to obtain a microcapsule composite flame retardant. Chinese patent document CN115895226 A provides a high nitrogen and phosphorus core-shell flame retardant and its preparation method and application, which uses polyurethane as the shell layer. These two technologies use polyurethane or melamine urea-formaldehyde resin as the shell layer to effectively coat the core, but the P and N elements still exist in this type of shell layer, which will cause the platinum catalyst to fail due to poisoning, thereby limiting the application of this flame retardant in addition silicone rubber.
[0006] Chinese patent document CN 118063857 A uses silicon-modified ammonium polyphosphate to coat melamine salt to obtain a core-shell flame retardant, but the modified ammonium polyphosphate is still hygroscopic, which affects the storage stability of the flame retardant.
[0007] Chinese patent document CN 109537300 A provides a method for preparing flame-retardant and smoke-suppressing silicone leather for aviation seats. This microcapsule composite flame retardant can be used directly in addition-type silicone rubber. However, during combustion, the flame retardant in the flame-retardant microcapsule continuously migrates and releases from the core material to the capsule wall, which will lead to uneven release of the flame retardant, affecting the stability and efficiency of the flame retardant effect. In addition, the preparation process is complicated and requires multiple washing and drying to remove unreacted monomers and by-products.
[0008] Therefore, it is very necessary to develop a flame retardant that has a small addition amount, good flame retardant properties, is environmentally friendly, and is not limited to application in addition-type silicone rubber. Summary of the invention
[0009] The purpose of the present invention is to prepare ammonium polyphosphate and titanium dioxide into a composite flame retardant filler by an in-situ polymerization method. Titanium dioxide can be used as a catalyst to promote the decomposition of ammonium polyphosphate and accelerate the flame retardant reaction. Under the condition of light, titanium dioxide can undergo a photocatalytic reaction to generate free radicals. These free radicals can react with free radicals generated during the combustion process to interrupt the combustion chain reaction and achieve the purpose of synergistic flame retardancy in the flame retardant process. In addition, the present invention uses organic polymers to coat ammonium polyphosphate-titanium dioxide to prepare a core-shell structure, avoiding direct contact between the platinum catalyst and the ammonium polyphosphate in the addition silicone rubber, preventing the platinum catalyst from being poisoned and losing its activity, and solving the problem of the application of phosphorus-nitrogen flame retardants in addition silicone rubber. At the same time, the organic polymer is screened to solve the problem of reduced flame retardant efficiency caused by coating.
[0010] In order to achieve the above object, the present invention is achieved through the following technical solutions:
[0011] A method for preparing a synergistic flame retardant with a core-shell structure comprises the following steps:
[0012] (1) heating phosphoric acid while stirring, adding urea when the temperature reaches 50-100° C., continuing stirring and heating; when the temperature reaches 120-150° C., adding titanium dioxide, maintaining the temperature and stirring, and then drying and crushing to obtain an ammonium polyphosphate-titanium dioxide composite;
[0013] (2) adding the ammonium polyphosphate-titanium dioxide composite into the organic polymer solution, stirring at room temperature, and heating to remove the solvent to obtain a synergistic flame retardant with a core-shell structure.
[0014] A further technical solution is that the molar ratio of the phosphoric acid to the urea is 1:1.2-2, preferably 1:1.6-1.8. The amount of titanium dioxide added is 10-20wt% of the total mass of the phosphoric acid and the urea, preferably 15-18wt%.
[0015] A further technical solution is that the mass ratio of the ammonium polyphosphate-titanium dioxide composite to the organic polymer solution is 20:80-200g, and the concentration of the organic polymer solution is 30-40wt%.
[0016] A further technical solution is that the melting point of the organic polymer is 80-180° C. The present invention cleverly designs the low melting point of the packaging material to ensure the stability and heat resistance of the product under normal conditions. When the packaging material is burned by fire, the core flame retardant material is quickly released and has extremely high flame retardancy.
[0017] Optionally, the organic polymer is one of polyethylene wax, polypropylene wax, polyvinyl chloride, and EVA.
[0018] Optionally, the solvent in the organic polymer solution is at least one of toluene, xylene, tetrahydrofuran, cyclohexane, and N,N-dimethylformamide, wherein toluene is preferably used as the solvent.
[0019] Furthermore, the method for preparing the organic polymer solution in step (2) is: slowly adding the organic polymer to the solvent, starting stirring and heating to ensure that the organic polymer is fully dissolved; when heated to the dissolution temperature of the organic polymer in the solvent, continue stirring for a period of time, and after it is fully dissolved, cool the solution to room temperature.
[0020] Optionally, the titanium dioxide particle size is 20 to 50 nm.
[0021] Optionally, in step (1), a three-necked flask is used as a reaction container and an ammonia outlet pipe is connected, the heating method is oil bath heating, the heat preservation and stirring time is 15 to 30 minutes, and the drying is cured in an oven at 190 to 230° C. for 2 to 3 hours; in step (2), the stirring time at room temperature is 3 to 5 hours, and the temperature is raised to 50 to 60° C. to remove the solvent. Further, the temperature is raised to 50 to 60° C. under a vacuum degree of ≤ 0.07 MPa to remove the solvent.
[0022] The synergistic flame retardant with a core-shell structure prepared by the above preparation method comprises ammonium polyphosphate, titanium dioxide, and an organic polymer. The ammonium polyphosphate and titanium dioxide form an ammonium polyphosphate-titanium dioxide composite, and the flame retardant uses the ammonium polyphosphate-titanium dioxide composite as a core and the organic polymer as a shell to form a core-shell structure.
[0023] The present invention also provides the application of the synergistic flame retardant with a core-shell structure, and the flame retardant is applied to addition-type silicone rubber to prepare silicone rubber products.
[0024] On the basis of the above technical solution, the present invention provides a method for preparing an optional synergistic flame retardant with a core-shell structure, comprising the following steps:
[0025] (1) Pour the calculated amount of phosphoric acid into a three-necked flask, connect the ammonia outlet pipe, heat and stir in an oil bath; control the heating rate at 2-5°C / min, add the calculated amount of urea when the temperature rises to 50-100°C, and continue heating and stirring; when the temperature rises to 120-150°C, add the calculated amount of titanium dioxide, keep warm and stir for 15-30 minutes; pour the obtained product into a tray, cure it in an oven at 190-230°C for 2-3 hours, and then crush the cured material to obtain a powder of ammonium polyphosphate-titanium dioxide composite;
[0026] (2) Pour the prepared organic polymer solution into a three-necked flask, add the ammonium polyphosphate-titanium dioxide complex obtained in step (1) according to the calculated amount, stir at room temperature for 3 to 5 hours, maintain the vacuum degree ≤ 0.07 MPa and heat to 50 to 60° C. to remove the solvent, and finally obtain a synergistic flame retardant with a core-shell structure, i.e., ammonium polyphosphate-titanium dioxide@organic polymer core-shell structure flame retardant.
[0027] Unless otherwise specified, in the present invention, room temperature refers to an ambient temperature of 15 to 40°C.
[0028] The principle of the present invention is as follows:
[0029] The present invention designs and synthesizes a core-shell structure synergistic flame retardant of ammonium polyphosphate-titanium dioxide coated with an organic polymer. Titanium dioxide can be used as a catalyst to promote the decomposition of ammonium polyphosphate and accelerate the flame retardant reaction; under the condition of light and heat, titanium dioxide can undergo a photocatalytic reaction to generate free radicals, which can react with free radicals generated in the combustion process to interrupt the combustion chain reaction and achieve the purpose of synergistic flame retardancy in the flame retardant process. Ammonium polyphosphate and titanium dioxide are prepared into a composite flame retardant filler by an in-situ polymerization method. In a synergistic flame retardant system, the combination of ammonium polyphosphate and titanium dioxide can produce a complementary effect and improve the flame retardant efficiency. However, the nitrogen and phosphorus elements in ammonium polyphosphate can cause the platinum catalyst in the addition-type silicone rubber to be poisoned and limit its use. Therefore, the present invention uses an organic polymer to coat ammonium polyphosphate-titanium dioxide to prepare a core-shell structure, which, on the one hand, hinders the direct contact between the platinum catalyst and the ammonium polyphosphate, preventing the platinum catalyst from being poisoned and losing its activity; on the other hand, the organic polymer melts during high-temperature combustion, so that the composite flame retardant ammonium polyphosphate-titanium dioxide is quickly released, thereby improving the flame retardant efficiency. In addition, the organic polymer shell layer selected by the present invention does not contain P and N elements, thus avoiding the problem of poisoning and failure of platinum catalyst in addition-type silicone rubber caused by flame retardant. This method of preparing composite flame retardant by in-situ polymerization of ammonium polyphosphate and titanium dioxide improves the flame retardant efficiency of the flame retardant, and the problem of poisoning of platinum catalyst in addition-type silicone rubber caused by phosphorus and nitrogen elements is solved by coating ammonium polyphosphate-titanium dioxide with organic polymer.
[0030] The beneficial effects of the present invention are:
[0031] (1) The melting point of the organic polymer selected in the present invention is in the range of 80 to 180° C., which ensures the stability of the product under normal conditions. When burned at high temperatures, it can quickly melt and release the core flame retardant, thereby improving the flame retardant efficiency.
[0032] (2) The organic polymer selected as the shell material of the present invention is non-hygroscopic and has good storage stability, and the shell material does not contain P and N elements, thereby avoiding the problem of platinum catalyst poisoning caused by the application of core-shell flame retardants in addition-type silicone rubber.
[0033] (3) The present invention adopts an in-situ polymerization method to combine ammonium polyphosphate and titanium dioxide to prepare a synergistic flame retardant. When used in addition-type silicone rubber, it has the characteristics of small addition amount and high flame retardant efficiency.
[0034] (4) The present invention uses organic polymer to coat ammonium polyphosphate-titanium dioxide to prepare a core-shell structure, which is used in addition-type silicone rubber to hinder the contact between the platinum catalyst and ammonium polyphosphate, thereby preventing the ammonium polyphosphate from poisoning the platinum catalyst and losing its activity. DETAILED DESCRIPTION
[0035] Example 1
[0036] (1) Pour 100g of phosphoric acid into a three-necked flask, connect the stirring device and the ammonia outlet pipe, and slowly heat and stir in an oil bath with temperature measurement. The heating rate is controlled at 3℃ / min. When the temperature rises to 70℃, add 180g of urea, the mass ratio of phosphoric acid to urea is 1:1.8, and continue to heat and stir; when the temperature rises to 130℃, add 45g of titanium dioxide, the amount of titanium dioxide added is 16wt% of the total mass of phosphoric acid and urea, and keep warm and stir for 30min. Pour the obtained product into a tray and cure it in an oven at 220℃ for 2h. After curing, crush the material, and the obtained powder is ammonium polyphosphate-titanium dioxide composite flame retardant.
[0037] (2) 100 g of polypropylene wax was slowly added to a toluene solvent to prepare a 35 wt % polypropylene wax toluene solution, and the temperature was raised with stirring. When the temperature reached 130° C., the mixture was stirred for 30 min at the temperature. After stirring evenly, the solution was cooled to room temperature.
[0038] (3) Weigh 160 g of the polypropylene wax toluene solution obtained in step (2) and pour it into a three-necked flask, add 20 g of ammonium polyphosphate-titanium dioxide obtained in step (1), stir at room temperature for 3 h, maintain the vacuum degree at ≤ 0.07 MPa, raise the temperature to 60° C. to remove the toluene solvent, and finally obtain ammonium polyphosphate-titanium dioxide@polypropylene wax core-shell structure flame retardant.
[0039] Example 2
[0040] (1) Pour 100g of phosphoric acid into a three-necked flask, connect the stirring device and the ammonia outlet pipe, and slowly heat and stir in an oil bath with temperature measurement. The heating rate is controlled at 3℃ / min. When the temperature rises to 80℃, add 120g of urea, the mass ratio of phosphoric acid to urea is 1:1.2, and continue to heat and stir; when the temperature rises to 120℃, add 35g of titanium dioxide, the amount of titanium dioxide added is 16wt% of the total mass of phosphoric acid and urea, and keep warm and stir for 30min. Pour the obtained product into a tray and cure it in an oven at 220℃ for 2h. After curing, crush the material, and the obtained powder is ammonium polyphosphate-titanium dioxide composite flame retardant.
[0041] (2) 100 g of polypropylene wax was slowly added to a toluene solvent to prepare a 32 wt % polypropylene wax toluene solution, and the temperature was raised with stirring. When the temperature reached 130° C., the mixture was stirred for 30 min at the temperature. After stirring evenly, the solution was cooled to room temperature.
[0042] (3) Weigh 160 g of the polypropylene wax toluene solution obtained in step (2) and pour it into a three-necked flask, add 20 g of ammonium polyphosphate-titanium dioxide obtained in step (1), stir at room temperature for 3 h, maintain the vacuum degree at ≤ 0.07 MPa, raise the temperature to 60° C. to remove the toluene solvent, and finally obtain ammonium polyphosphate-titanium dioxide@polypropylene wax core-shell structure flame retardant.
[0043] Example 3
[0044] (1) Pour 100g of phosphoric acid into a three-necked flask, connect the stirring device and the ammonia outlet pipe, and slowly heat and stir in an oil bath with temperature measurement. The heating rate is controlled at 4℃ / min. When the temperature rises to 70℃, add 160g of urea, the mass ratio of phosphoric acid to urea is 1:1.6, and continue to heat and stir; when the temperature rises to 140℃, add 50g of titanium dioxide, the amount of titanium dioxide added is 19.2wt% of the total mass of phosphoric acid and urea, and keep warm and stir for 30min. Pour the obtained product into a tray and cure it in an oven at 200℃ for 3h. After curing, crush the material, and the obtained powder is ammonium polyphosphate-titanium dioxide composite flame retardant.
[0045] (2) 100 g of polypropylene wax was slowly added to a toluene solvent to prepare a 35 wt % polypropylene wax toluene solution, and the temperature was raised with stirring. When the temperature reached 130° C., the mixture was stirred for 30 min at the temperature. After stirring evenly, the solution was cooled to room temperature.
[0046] (3) Weigh 160 g of the polypropylene wax toluene solution obtained in step (2) and pour it into a three-necked flask, add 20 g of ammonium polyphosphate-titanium dioxide obtained in step (1), stir at room temperature for 3 h, maintain the vacuum degree at ≤ 0.07 MPa, raise the temperature to 60° C. to remove the toluene solvent, and finally obtain ammonium polyphosphate-titanium dioxide@polypropylene wax core-shell structure flame retardant.
[0047] Example 4
[0048] (1) Pour 100g of phosphoric acid into a three-necked flask, connect the stirring device and the ammonia outlet pipe, and slowly heat and stir in an oil bath with temperature measurement. The heating rate is controlled at 3℃ / min. When the temperature rises to 70℃, add 200g of urea, the mass ratio of phosphoric acid to urea is 1:2, and continue to heat and stir; when the temperature rises to 140℃, add 30g of titanium dioxide, the amount of titanium dioxide added is 10wt% of the total mass of phosphoric acid and urea, and keep warm and stir for 20min. Pour the obtained product into a tray and cure it in an oven at 220℃ for 2h. After curing, crush the material, and the obtained powder is ammonium polyphosphate-titanium dioxide composite flame retardant.
[0049] (2) 100 g of polypropylene wax was slowly added to a toluene solvent to prepare a 38 wt % polypropylene wax toluene solution, and the temperature was raised with stirring. When the temperature reached 130° C., the mixture was stirred for 30 min at the temperature. After stirring evenly, the solution was cooled to room temperature.
[0050] (3) Weigh 160 g of the polypropylene wax toluene solution obtained in step (2) and pour it into a three-necked flask, add 20 g of ammonium polyphosphate-titanium dioxide obtained in step (1), stir at room temperature for 3 h, maintain the vacuum degree at ≤ 0.07 MPa, and heat to 60° C. to remove the toluene solvent, and finally obtain ammonium polyphosphate-titanium dioxide@polypropylene wax core-shell structure flame retardant.
[0051] Example 5
[0052] (1) Pour 100g of phosphoric acid into a three-necked flask, connect the stirring device and the ammonia outlet pipe, and slowly heat and stir in an oil bath with temperature measurement. The heating rate is controlled at 3℃ / min. When the temperature rises to 70℃, add 180g of urea, the mass ratio of phosphoric acid to urea is 1:1.8, and continue to heat and stir; when the temperature rises to 130℃, add 45g of titanium dioxide, the amount of titanium dioxide added is 16wt% of the total mass of phosphoric acid and urea, and keep warm and stir for 30min. Pour the obtained product into a tray and cure it in an oven at 220℃ for 2h. After curing, crush the material, and the obtained powder is ammonium polyphosphate-titanium dioxide composite flame retardant.
[0053] (2) Take 100g of polyethylene wax and slowly add it into xylene solvent to prepare a polyethylene wax xylene solution with a concentration of 35wt%, heat it and stir it. When the temperature reaches 100°C, keep it warm and stir it for 30 minutes. After stirring evenly, cool the solution to room temperature.
[0054] (3) Weigh 160 g of the polyethylene wax xylene solution obtained in step (2) and pour it into a three-necked flask, add 20 g of the ammonium polyphosphate-titanium dioxide obtained in step (1), stir at room temperature for 3 h, maintain the vacuum degree at ≤ 0.07 MPa, and heat to 50° C. to remove the xylene solvent, and finally obtain the ammonium polyphosphate-titanium dioxide@polyethylene wax core-shell structure flame retardant.
[0055] Example 6
[0056] (1) Pour 100g of phosphoric acid into a three-necked flask, connect the stirring device and the ammonia outlet pipe, and slowly heat and stir in an oil bath with temperature measurement. The heating rate is controlled at 3℃ / min. When the temperature rises to 80℃, add 140g of urea, the mass ratio of phosphoric acid to urea is 1:1.4, and continue to heat and stir; when the temperature rises to 130℃, add 30g of titanium dioxide, the amount of titanium dioxide added is 12.5wt% of the total mass of phosphoric acid and urea, and keep warm and stir for 30min. Pour the obtained product into a tray and cure it in an oven at 210℃ for 2h. After curing, crush the material, and the obtained powder is ammonium polyphosphate-titanium dioxide composite flame retardant.
[0057] (2) Take 100g of polyethylene wax and slowly add it into xylene solvent to prepare a polyethylene wax xylene solution with a concentration of 35wt%, heat it and stir it. When the temperature reaches 100°C, keep it warm and stir it for 30 minutes. After stirring evenly, cool the solution to room temperature.
[0058] (3) Weigh 160 g of the polyethylene wax xylene solution obtained in step (2) and pour it into a three-necked flask, add 20 g of the ammonium polyphosphate-titanium dioxide obtained in step (1), stir at room temperature for 3 h, maintain the vacuum degree at ≤ 0.07 MPa, and heat to 50° C. to remove the xylene solvent, and finally obtain the ammonium polyphosphate-titanium dioxide@polyethylene wax core-shell structure flame retardant.
[0059] Example 7
[0060] (1) The ammonium polyphosphate-titanium dioxide composite flame retardant was prepared by the method of step (1) of Example 1.
[0061] (2) Take 100g EVA (ethylene-vinyl acetate copolymer) and slowly add it into N,N-dimethylformamide solvent to prepare a 35wt% EVA N,N-dimethylformamide solution. Heat and stir. When the temperature reaches 90°C, keep stirring for 30 minutes. After stirring evenly, cool the solution to room temperature.
[0062] (3) Weigh 160 g of the EVA N,N-dimethylformamide solution obtained in step (2) and pour it into a three-necked flask, add 20 g of the ammonium polyphosphate-titanium dioxide obtained in step (1), stir at room temperature for 3 h, maintain the vacuum degree at ≤ 0.07 MPa, and heat to 50° C. to remove the N,N-dimethylformamide solvent, and finally obtain the ammonium polyphosphate-titanium dioxide@EVA core-shell structure flame retardant.
[0063] Comparative Example 1
[0064] Pour 100g of phosphoric acid into a three-necked flask, connect the stirring device and the ammonia outlet pipe, and slowly heat and stir in an oil bath with temperature measurement. The heating rate is controlled at 3℃ / min. When the temperature rises to 70℃, add 180g of urea, the mass ratio of phosphoric acid to urea is 1:1.8, and continue to heat and stir; when the temperature rises to 130℃, add 45g of titanium dioxide, the amount of titanium dioxide added is 16wt% of the total mass of phosphoric acid and urea, and keep warm and stir for 30min. Pour the obtained product into a tray and cure it in a 220℃ oven for 2h. After curing, crush the material to obtain an ammonium polyphosphate-titanium dioxide composite flame retardant.
[0065] Comparative Example 2
[0066] (1) 100 g of polypropylene wax was slowly added to a toluene solvent to prepare a 35 wt % polypropylene wax toluene solution, and the temperature was raised with stirring. When the temperature reached 130° C., the mixture was stirred for 30 min at the temperature. After stirring evenly, the solution was cooled to room temperature.
[0067] (2) Weigh 160 g of the polypropylene wax toluene solution obtained in step (1) and pour it into a three-necked flask, add 20 g of titanium dioxide, stir at room temperature for 3 h, maintain the vacuum degree at ≤ 0.07 MPa, and heat to 60° C. to remove the toluene solvent, and finally obtain a titanium dioxide @ polypropylene wax core-shell structure flame retardant.
[0068] Comparative Example 3
[0069] 5g of commercially available aluminum hydroxide flame retardant.
[0070] Comparative Example 4
[0071] 40 g of the same commercially available aluminum hydroxide flame retardant as in Comparative Example 3.
[0072] Comparative Example 5
[0073] (1) Pour 100g of phosphoric acid into a three-necked flask, connect the stirring device and the ammonia outlet pipe, and slowly heat and stir in an oil bath with temperature measurement. The heating rate is controlled at 3℃ / min. When the temperature rises to 70℃, add 220g of urea, the mass ratio of phosphoric acid to urea is 1:2.2, and continue to heat and stir; when the temperature rises to 140℃, add 20g of titanium dioxide, the amount of titanium dioxide added is 6.25wt% of the total mass of phosphoric acid and urea, and keep warm and stir for 30min. Pour the obtained product into a tray and cure it in an oven at 220℃ for 2h. After curing, crush the material, and the obtained powder is ammonium polyphosphate-titanium dioxide composite flame retardant.
[0074] (2) 100 g of polypropylene wax was slowly added to a toluene solvent to prepare a 35 wt % polypropylene wax toluene solution, and the temperature was raised with stirring. When the temperature reached 130° C., the mixture was stirred for 30 min at the temperature. After stirring evenly, the solution was cooled to room temperature.
[0075] (3) Weigh 160 g of the polypropylene wax toluene solution obtained in step (2) and pour it into a three-necked flask, add 20 g of ammonium polyphosphate-titanium dioxide obtained in step (1), stir at room temperature for 3 h, maintain the vacuum degree at ≤ 0.07 MPa, and heat to 60° C. to remove the toluene solvent, and finally obtain ammonium polyphosphate-titanium dioxide@polypropylene wax core-shell structure flame retardant.
[0076] Comparative Example 6
[0077] (1) The ammonium polyphosphate-titanium dioxide composite flame retardant was prepared by the method of step (1) of Example 1.
[0078] (2) Take 100g of polyvinyl alcohol and slowly add it into xylene solvent to prepare a polyvinyl alcohol xylene solution with a concentration of 35wt%, heat it and stir it. When the temperature reaches 130°C, keep it warm and stir it for 30 minutes. After stirring evenly, cool the solution to room temperature.
[0079] (3) Weigh 160 g of the polyvinyl alcohol xylene solution obtained in step (2) and pour it into a three-necked flask, add 20 g of the ammonium polyphosphate-titanium dioxide obtained in step (1), stir at room temperature for 3 h, maintain the vacuum degree at ≤ 0.07 MPa, and heat to 60° C. to remove the xylene solvent, and finally obtain the ammonium polyphosphate-titanium dioxide@polyvinyl alcohol core-shell structure flame retardant.
[0080] Comparative Example 7
[0081] (1) The ammonium polyphosphate-titanium dioxide composite flame retardant was prepared by the method of step (1) of Example 1.
[0082] (2) Add water to polyethyleneimine to prepare a solution with a concentration of 8 wt %; add water to glutaraldehyde to prepare a solution with a concentration of 5 wt %; add 20 g of the glutaraldehyde solution to 120 g of the polyethyleneimine solution, stir thoroughly, heat to 80° C. and keep warm to obtain a prepolymer solution.
[0083] (3) Weigh 160 g of the prepolymer solution obtained in step (2) and pour it into a three-necked flask, add 20 g of the ammonium polyphosphate-titanium dioxide obtained in step (1), and stir the polymerization reaction at 80° C. to ensure that the pH value of the reaction system is 4. After reacting for 3 hours, adjust the pH value to 7.5, let it stand and then centrifuge, wash with water and anhydrous ethanol in turn, and dry to finally obtain an ammonium polyphosphate-titanium dioxide@polyethyleneimine cross-linked core-shell structure flame retardant.
[0084] Test method:
[0085] The flame retardant performance test of the flame retardants in the above-mentioned Examples 1 to 7 and Comparative Examples 1 to 7 comprises the following steps:
[0086] Sample preparation: weigh 92g of vinyl silicone oil with a viscosity of 1000cs, add 5g of the flame retardant in the embodiment or comparative example (wherein the amount of aluminum hydroxide added in Comparative Example 4 is 40g), stir evenly, then add 4g of hydrogen-containing silicone oil with a hydrogen content of 0.36%, 0.06g of ethynyl cyclohexanol, stir evenly, then add 0.3g of Custer platinum, stir evenly, pour into a flat vulcanizer for vulcanization, take out after curing for 30 minutes, and make it into a standard test piece.
[0087] Test: The flame retardant properties of the addition silicone rubber materials obtained in Examples 1-7 and Comparative Examples 1-7 were tested respectively according to GB / T 2408-2008 standard. The test results are shown in Table 1.
[0088] Table 1 Flame retardant test results of silicone rubber
[0089]
[0090] Note: T1 is the first afterflame time; T2 is the second afterflame time; T3 is the second afterglow time. The amount of titanium dioxide added refers to the ratio of the mass of titanium dioxide to the total mass of phosphoric acid and urea.
[0091] From T1, T2, and T3, it can be seen that the T1 time of Example 1, Example 5, and Example 7 is short, and the T2 and T3 times are relatively long, indicating that the organic polymer selected as the shell layer of the present invention melts quickly during combustion, and the flame retardant in the shell quickly takes effect.
[0092] As can be seen from Table 1, the flame retardant grade of Example 1 is V-0. 2When the addition amount is not within the preferred data range, it is difficult for the addition silicone rubber material to achieve V-0 flame retardant effect. The reason is that during the reaction, when the proportion of urea is small, it cannot provide enough ammonia, the condensation reaction is incomplete, and ammonium polyphosphate cannot be effectively generated; when the proportion of urea is large, a large amount of urea is easily generated at high temperature, and ammonium polyphosphate cannot be effectively generated. In addition, when TiO 2 When the added amount is not within the preferred range, it cannot form an effective synergistic flame retardant effect with ammonium polyphosphate.
[0093] It can be clearly seen from Comparative Examples 1-4 that in Comparative Example 1, uncoated ammonium polyphosphate-titanium dioxide is added to the silicone rubber, and the silicone rubber cannot be cured normally; in Comparative Example 2, only the flame retardant coated with titanium dioxide is added, and the flame retardant effect is poor. The silicone rubber burns completely within 63 seconds and the burning products fall off; in Comparative Example 3, 5 parts of commercially available aluminum hydroxide flame retardant are added, and the silicone rubber has no flame retardant effect. The silicone rubber burns completely within 57 seconds and the burning products fall off; in Comparative Example 4, when 40 parts of commercially available aluminum hydroxide flame retardant are added, the flame retardant grade reaches V0.
[0094] In Comparative Example 5, the ratio of phosphoric acid to urea is 1:2.2, and TiO 2 The addition amount is 6wt% of the total mass of phosphoric acid and urea, and the silicone rubber has no flame retardant effect. It can be concluded that when the ratio of phosphoric acid, urea, TiO 2 When the added amount is not within the scope of the present invention, there is no flame retardant effect.
[0095] Comparative Example 1, Comparative Example 6, and Comparative Example 7, wherein Comparative Example 6 uses polyvinyl alcohol as the shell layer. Since polyvinyl alcohol is easily hygroscopic, the shell layer is easily damaged during long-term storage, resulting in unstable storage performance; Comparative Example 7 uses polyethyleneimine cross-linked material as the shell layer. Since its shell layer contains P and N elements, the activity of the platinum catalyst is affected, thereby causing the glue to fail to cure normally.
[0096] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A method for preparing a synergistic flame retardant having a core-shell structure, characterized in that: The following steps are involved: (1) heating phosphoric acid while stirring, adding urea when the temperature reaches 50-100° C., continuing stirring and heating; when the temperature reaches 120-150° C., adding titanium dioxide, maintaining the temperature and stirring, and then drying and crushing to obtain an ammonium polyphosphate-titanium dioxide composite; (2) adding the ammonium polyphosphate-titanium dioxide composite into the organic polymer solution, stirring at room temperature, and heating to remove the solvent to obtain a synergistic flame retardant with a core-shell structure.
2. The method for preparing a synergistic flame retardant having a core-shell structure according to claim 1, characterized in that: The molar ratio of the phosphoric acid to the urea is 1:1.2-2, and the added amount of the titanium dioxide is 10-20 wt % of the total mass of the phosphoric acid and the urea.
3. The method for preparing a synergistic flame retardant having a core-shell structure according to claim 2, characterized in that: The mass ratio of the ammonium polyphosphate-titanium dioxide composite to the organic polymer solution is 20:80-200 g, and the concentration of the organic polymer solution is 30-40 wt %.
4. The synergistic flame retardant with a core-shell structure according to claim 3, characterized in that: The melting point of the organic polymer is 80-180°C.
5. The synergistic flame retardant with a core-shell structure according to claim 4, characterized in that: The organic polymer is one of polyethylene wax, polypropylene wax, polyvinyl chloride and EVA.
6. The method for preparing a synergistic flame retardant having a core-shell structure according to claim 5, characterized in that: The solvent in the organic polymer solution is at least one of toluene, xylene, tetrahydrofuran, cyclohexane and N,N-dimethylformamide.
7. The synergistic flame retardant with a core-shell structure according to claim 6, characterized in that: The particle size of the titanium dioxide is 20 to 50 nm.
8. The method for preparing a synergistic flame retardant having a core-shell structure according to claim 7, characterized in that: In step (1), a three-necked flask is used as a reaction container and an ammonia outlet pipe is connected. The heating method is oil bath heating, the insulation stirring time is 15 to 30 minutes, and the drying is carried out in an oven at 190 to 230° C. for curing for 2 to 3 hours. In step (2), the stirring time at room temperature is 3 to 5 hours, and the temperature is raised to 50 to 60° C. to remove the solvent.
9. A flame retardant obtained by the method for preparing a synergistic flame retardant with a core-shell structure according to any one of claims 1 to 8.
10. The use of the synergistic flame retardant with a core-shell structure according to claim 9, characterized in that: The flame retardant is applied to addition-type silicone rubber to prepare silicone rubber products.
Citation Information
Cited By
Preparation method of lycopodium powder coated ammonium polyphosphate flame retardant
CN122080500A